Irishness and womanhood in nineteenth-century British writing - Tracy, Thomas (Thomas J.) (Ashgate, 2009)
Using Lady Morgan's The Wild Irish Girl as his point of departure, Thomas J. Tracy argues that nineteenth-century debates over what constitutes British national identity often revolved around representations of Irishness, especially Irish womanhood. He maps the genealogy of this development in fiction, political discourse, and the popular press, from Edgeworth's Castle Rackrent through Trollope's Irish novels, focusing on the pivotal period from 1806 through the 1870s.